Pengembangan Perangkat Pembelajaran Berbasis E-Komik Kelas V SDN 205 Palembang - eny; aldora pratama; Liza Murniviyanti (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2023)
The purpose of this research was to find out the process of developing E-Comic-based learning media in class V SDN 205 Palembang. To find out student responses and feasibility in using E-Comic in fifth grade students. The type of research used in this research is the Research and Development (R&D) method with the ADDIE development model. Questionnaire data collection techniques, tests, and documentation. Data analysis techniques were carried out to obtain E-Comics according to student response criteria and eligibility. The results of this study are that the development of E-Comic media is declared valid or feasible, based on the results of the validity assessment according to media experts the average score is 4.3 with a percentage of 84.8%, the category is very valid, linguists average score is 4 with a percentage of 80 % category is very valid and material expert average score is 4.4 with a percentage of 94.5% category is very valid. The development of E-Comic media was stated to be practical based on the results of the practicality assessment according to the student response questionnaire getting an average score of 4.2 percentages 84.5 in the very practical category.